IMF Committee on Balance of Payments Statistics : Annual Report 2019 - Sanchez-Munoz, Carlos (Balance of Payments Statistics; Balance of Payments Statistics ;, 2020)
The 2019 Annual Report of the IMF Committee on Balance of Payments Statistics (the Committee) provides an overview of recent trends in global balance of payments and international investment position statistics, summarizes the Committee's work during 2019, and presents the work program of the Committee in the coming year.